Outplacement: The Polish Experience and Plans for Development in the Labour Market - Andrzej Klimczuk; Magdalena Klimczuk-Kochańska (The European Social Model Adrift: Europe, Social Cohesion and the Economic Crisis, 2015)
This chapter focuses on maintaining employment in the sector of small and medium-sized enterprises, which is crucial for the functioning of the economy. However, in an economic crisis, the changes in the area of employment of workers often become the foremost way of adapting to declining financial resources, which are the result of reduction of interest in the offer of the organisation by the customers. These actions had proven to be particularly evident in the case of global financial and economic crisis, which also affected the Polish economy after 2008. The chapter suggests that the layoffs lead to rise in unemployment. Thus, there is a need to promote the outplacement, which is, a technique oriented on responsible dismissals in order to support a smooth transition of laid-off workers to new workplaces. In this way, both employees and companies increase their chances of maintaining competencies and better adapt to market competition requirements. This chapter explores the characteristics of the labour market policy in Poland, main features of the outplacement in the context of the crisis, examples of the outplacement implementation, plans for further development of the outplacement, and conclusions including directions for further research.
Keywords: E24; J14; J28; J68; 330; Unemployment; Activation; Workfare; Public Private Partnerships; Social cohesion; Labour market policy; Partnerships; Labour markets; Restructuring; Workfare; Outplacement; Cross-sectoral Cooperation